The inclusive management strategy : engineering culture change for employees with disabilities - Fawzy, Camelia, 1973-; Shore, Brenda (Emerald Publishing Limited, 2019)
Every person has the potential to contribute to an organization as long as they have access to the right opportunities and connections, yet it sometimes is all too obvious that the stigma associated with a person's disability can have a negative impact on their ability to develop healthy work relationships with peers and supervisors. This situation can only be remedied through effective change management, a systematic approach to designing, implementing, and measuring progress on unique culture-change goals. Here Camelia Fawzy and Brenda Shore draw upon more than 40 years of research and practical business experience to support leaders and managers' efforts in transforming organizations and providing inclusive work opportunities for people with disAbilities (PwDs). What Fawzy and Shore offer is The Inclusive Management Strategy (IMS), an innovative approach to evaluating culture-change needs and to designing and implementing change solutions that address unique needs in order to create authentically inclusive social work-environments for PwDs. They address stigmatized differences associated with disabilities that lead to reducing fear, resentment, and anxiety in the organizational climate, ultimately arguing that culture change can only be achieved when most of our employees are engaged in a mind-change process, a conscious effort to change stigmatizing views associated with differences that need to be accommodated. For the practical, implementable plans of action it offers, The Inclusive Management Strategy is a must-read for managers and supervisors involved with policy, decision-making, strategy, and daily accommodations for PwDs.